THE IMPACT OF INFORMATION ATTACKS ON CHILDREN'S UPbringing IN THE FAMILY IN THE ERA OF MODERN GLOBALIZATION AND DIGITAL TECHNOLOGIES (Universal International Scientific Journal, 2026)
This article studies the formation of gender stereotypes within the framework of family psychology, their impact on child rearing and the social consciousness of the younger generation. The role of the family in the formation of moral and ethical immunity in the context of information attacks (radical ideas spread through the media, social networks, immoral content) is analyzed. The results of the study show that a democratic upbringing style based on gender equality in the family develops critical thinking, empathy and selective information perception skills in children, increasing psychological resilience to information attacks. Traditional gender stereotypes (man - strong breadwinner, woman - housewife) can cause self-doubt and difficulties in social adaptation in children. The article provides suggestions for reducing the negative impact of gender stereotypes in Uzbek families.
Keywords: family psychology, gender stereotypes, child rearing, moral and spiritual immunity, information overload, social consciousness, gender equality.